PERAN GURU KELAS DALAM PEMBELAJARAN SISWA SLOW LEARNER DI MADRASAH IBTIDAIYAH AR-ROIHAN LAWANG MALANG / THE ROLE OF THE CLASS TEACHER IN THE LEARNING OF SLOW LEARNER STUDENTS AT MADRASAH IBTIDAIYAH AR-ROIHAN LAWANG MALANG - Nadia Agustin; Rosidin (STAI Ma'had Aly Al-Hikam Malang, 2024)
Slow learner students fall into the category of Children with Special Needs (CwSN) who have intellectual disabilities with an IQ score of 70-90, so they require longer study time. This article was based on qualitative approach and case study type of research at Madrasah Ibtidaiyah (MI) Ar-Roihan, Lawang District, Malang Regency. Data was obtained through participant-observation techniques, semi-structured interviews and documentation, then analyzed using the Miles, Huberman and Saldana interactive model. There are two findings of the article. First, the implementation of slow learner student learning at MI Ar-Roihan consists of the planning, implementation and learning assessment phases. Second, the Class Teacher have five roles in the learning of slow learner students at MI Ar-Roihan: a) As administrator, the Class Teacher prepares Instructional Teaching for slow learner students who follow the regular curriculum. For slow learner students who follow the modified curriculum, the Instructional Teaching are prepared by the Special Assistant Teacher (SAT) after communicating with the Class Teacher; b) As facilitator, the Class Teacher determines teaching materials and learning methods for slow learner students who follow the regular curriculum. For slow learner students who follow the modified curriculum, teaching materials and learning methods are determined by SAT; c) As teacher, the Class Teacher provides classical learning material to all students, including slow learner students. Then, each SAT will repeat the explanation to the slow learner students, according to their characteristics and needs; d) As educator, the Class Teachers collaborate with SAT to educate Islamic character values, such as honesty and self-confidence, to slow learner students; e) As evaluator, Class Teacher is in charge of compiling general report for regular students and CwSN. Meanwhile, SAT is in charge of compiling assessment reports for slow learner students only. Keywords: Special Assistant Teacher (GPK), Class Teacher, MI Ar-Roihan, Inclusive Education, Slow Learner.